Jakub Pawliczak, Zarejestrowany związek partnerski a małżeństwo, seria Monografie LEX, Wydawnictwo Wolters Kluwer SA, Warszawa 2014, ss. 400, ISBN 978-83-264-3370-2 - Jankowska, Paulina (Studia Prawa Publicznego, 2019)
Jakub Pawliczak, Zarejestrowany związek partnerski a małżeństwo, seria Monografie LEX, Wydawnictwo Wolters Kluwer SA, Warszawa 2014, ss. 400, ISBN 978-83-264-3370-2